A non-metallic PEEK topology optimization reconstruction implant for large mandibular continuity defects, validated using the MANDYBILATOR apparatus - Bram B. J. Merema; Frederik K. L. Spijkervet; Joep Kraeima; Max J. H. Witjes (Scientific Reports)
Abstract In cases of large mandibular continuity defects resulting from malignancy resection, the current standard of care involves using patient-specific/custom titanium reconstruction plates along with autogenous grafts (fibula, scapula, or iliac crest segments). However, when grafts are not feasible or desired, only the reconstruction plate is used to bridge the gap. Unfortunately, metal osteosynthesis and reconstruction plates, including titanium, exhibit adverse effects such as stress-shielding and limitations in accurate postoperative irradiation (especially with proton-beam therapy). To address these issues, in this study we explore, develop and validate a non-metallic solution: a topology-optimized polyetheretherketone (PEEK) load-bearing implant for large non-grafted mandibular continuity defects. In order to thoroughly validate the developed PEEK reconstruction, a dedicated MANDYBILATOR testing apparatus was developed. Using the MANDYBILATOR finite element analysis results of the implant were confirmed and the PEEK implant was mechanically validated for both static and dynamic loading. Results show that the PEEK reconstructed mandible is comparably strong as the unreconstructed mandible and is unlikely to fail due to fatigue. Our PEEK implant design has the mechanical potential to act as a substitute for the current titanium plates used in the reconstruction of continuity defects of the mandible. This may potentially lead to optimised patient-specific reconstructions, with the implants matching the bone’s stiffness and possessing radiolucent properties which are useful for radiographic follow-ups and radiotherapy. Furthermore, the addition of the dynamic/cyclic MANDYBILATOR apparatus allows for more realistic application of the in-vivo loading of the mandible and can provide added insights in biomechanical behaviour of the mandible.